A SOLUTION METHOD FOR INTEGRO-DIFFERENTIAL EQUATIONS OF CONFORMABLE FRACTIONAL DERIVATIVE - Bayram, Mustafa; Hatipoglu, Veysel Fuat; Alkan, Sertan; Das, Sebahat Ebru (VINCA INST NUCLEAR SCI, 2018)
The aim of this work is to determine an approximate solution of a fractional order Volterra-Fredholm integro-differential equation using by the Sinc-collocation method. Conformable derivative is considered for the fractional derivatives. Some numerical examples having exact solutions are approximately solved. The comparisons of the exact and the approximate solutions of the examples are presented both in tables and graphical forms.
Keywords: Sinc-collocation method; conformable fractional derivative; Volterra-Fredholm integro-differential equation; Thermodynamics